Collaborative passenger flow control on an oversaturated metro line: a path choice approach. Issue 1 (2nd January 2020) - Meng, Fanting; Yang, Lixing; Wei, Yun; Li, Shukai; Gao, Ziyou; Shi, Jungang
Abstract : Focusing on reducing the traffic congestion on an oversaturated urban metro system, this study investigates the collaborative passenger flow control problem for a metro line. By introducing the timetable-oriented space-time network representation, the problem of interest is finally formulated as an integer programming model, in which the objective function aims to minimize the total weighted passenger waiting time at different stations. Since the final decision is closely related to the space-time path-finding process, the proposed model can also be regarded as a coordinated path-finding process with train loading capacity constraints. Then, an efficient heuristic algorithm is developed to solve the proposed model. Finally, a series of numerical examples are implemented on a sample metro line and the Beijing Batong metro line. The computational results show that the proposed approach can produce high-quality passenger flow control strategies for the metro system, thereby demonstrating the effectiveness of the proposed model and algorithm.